Thromboembolic complications after upper abdominal cancer surgery at the University hospital of North Norway - Høgstad, Ida Elise (UiT Norges arktiske universitet, 2020)
Background: Venous thromboembolism (VTE) is a serious and potentially fatal complication after surgery. Operations for malignancy in the upper abdomen are traditionally regarded as especially prone to such complications. Antithrombotic prophylaxis with low weight molecular heparing (LWMH) before and after surgery has been shown to significantly reduce the risk for VTE complications. Recommended duration of antithrombotic prophylaxis after abdominal cancer surgery is 28 days. Many clinicians argue that antithrombotic prophylaxis until the patient is fully mobilized is sufficient. The primary object of this thesis was to investigate the safety of short-term antithrombotic prophylaxis and the risk of developing VTE after major upper abdominal cancer surgery. Method: This was a retrospective study of 493 patients undergoing elective surgery for cancer in the eosophagus, stomach, pancreas, liver, gallbladder and biliary tract at University Hospital of North Norway (UNN) Tromsø between 2013 and 2018. Patients which had a VTE while receiving antithrombotic prophylaxis, received antithrombotic prohpylaxis for more than 28 days, died within 90 days, were anticoagulated with vitamin K antagonists, LMWH or new oral anticoagulants before surgery, underwent minor surgery or were transferred to another hospital while still receiving antithrombotic prophylaxis, were excluded. Main outcome was symptomatic VTE diagnosed within 90 days after surgery. Results: A total of 243 patients were excluded from the main study group. For the remaining 250 patients, five had a non-fatal VTE incident within 90 days of surgery (2%). Conclusion: Five out of 250 patients (2%) who received antithrombotic profylaxis for less than 28 days suffered from VTE complications within 90 days after surgery. This study highlights the importance of sufficient VTE profylaxis after major upper abdominal cancer surgery.